A Phenotypic Approach for the Identification of New Molecules for Targeted Protein Degradation Applications. (August 2021) - Stacey, Peter; Lithgow, Hannah; Lewell, Xiao; Konopacka, Agnieszka; Besley, Stephen; Green, Georgina; Whatling, Ryan; Law, Robert; Röth, Sascha; Sapkota, Gopal P.; Smith, Ian E. D.; Burley, Glenn A.; et al.
Targeted protein degradation is an emerging new strategy for the modulation of intracellular protein levels with applications in chemical biology and drug discovery. One approach to enable this strategy is to redirect the ubiquitin–proteasome system to mark and degrade target proteins of interest (POIs) through the use of proteolysis targeting chimeras (PROTACs). Although great progress has been made in enabling PROTACs as a platform, there are still a limited number of E3 ligases that have been employed for PROTAC design. Herein we report a novel phenotypic screening approach for the identification of E3 ligase binders. The key concept underlying this approach is the high-throughput modification of screening compounds with a chloroalkane moiety to generate HaloPROTACs in situ, which were then evaluated for their ability to degrade a GFP-HaloTag fusion protein in a cellular context. As proof of concept, we demonstrated that we could generate and detect functional HaloPROTACs in situ, using a validated Von Hippel–Lindau (VHL) binder that successfully degraded the GFP-HaloTag fusion protein in living cells. We then used this method to prepare and screen a library of approximately 2000 prospective E3 ligase-recruiting molecules.